2017
DOI: 10.1007/s11356-017-9642-9
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal, placental, and umbilical cord blood parameters in pregnant women residing in areas with intensive pesticide application

Abstract: In rural populations, the proximity to areas with intensive pesticide application represents a risk factor of xenobiotic exposure. Here, we investigated whether newborns born to mothers residing in an area with intensive pesticide application show alterations in placental and neonatal morphometric standards, umbilical cord blood (UCB) biochemical parameters, and/or biomarkers related to oxidative stress and oxidative damage. Samples were collected from 151 healthy pregnant women residing in a rural area (rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 46 publications
1
4
0
2
Order By: Relevance
“…24,25 We hypothesize that the hematological difference can be related to the environmental factor, although the study of Quintana reported that this factor doesn't have a significant differences in the UCB hemogram parameters. 26 Comparing with previously reported data from population, geographically or genetically close to Tunisia, the hematological parameters determined in our study are quite different (►Table 4). This may be due to several factors such as size sample and ethnic origin.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…24,25 We hypothesize that the hematological difference can be related to the environmental factor, although the study of Quintana reported that this factor doesn't have a significant differences in the UCB hemogram parameters. 26 Comparing with previously reported data from population, geographically or genetically close to Tunisia, the hematological parameters determined in our study are quite different (►Table 4). This may be due to several factors such as size sample and ethnic origin.…”
Section: Discussionsupporting
confidence: 60%
“…24 25 We hypothesize that the hematological difference can be related to the environmental factor, although the study of Quintana reported that this factor doesn't have a significant differences in the UCB hemogram parameters. 26…”
Section: Discussionmentioning
confidence: 99%
“…No estudo de Quintana et al 24 foram observados os parâmetros neonatais, placentários e do sangue do cordão umbilical em mulheres grávidas que residem em áreas com aplicação intensiva de pesticidas. Em populações rurais, a proximidade de áreas com aplicação intensiva de agrotóxicos representa um fator de risco de exposição a xenobióticos.…”
Section: Resultsunclassified
“…As amostras foram coletadas de 151 mulheres grávidas saudáveis residentes em uma área rural durante as temporadas de pulverização de pesticidas (GRSS) e não pulverização (GRNSS), bem como de mulheres de uma população urbana (grupo controle; CG) e agrupadas de acordo com o tipo de parto (vaginal ou cesáreo). No grupo de parto vaginal, o peso placentário e o índice placentário foram maiores nos grupos GR do que no GC (p = 0,01), enquanto no grupo parto cesáreo o peso do recém-nascido foi menor no grupo GRSS do que no GC 24 .…”
Section: Resultsunclassified
“…Other papers have exploited seasonal variation in the application of pesticides by comparing seasonally exposed and non-exposed households, finding that seasonally exposed households have higher concentrations of pesticide metabolites in urine samples and a decrease in nervous system functioning (Bradman et al, 2011;Cecchi et al, 2012;Galea et al, 2015;Quintana et al, 2017). 10 The medical literature has also shown that exposure to pesticides during gestation can cause intrauterine growth restriction, weight problems and birth defects.…”
Section: Pesticides and Healthmentioning
confidence: 99%